Moral sensitivity in the practice of Family Health Strategy professionals - Cecília Maria Lima Cardoso Ferraz; Gláucia de Souza Vilela; Danielle de Araújo Moreira; Maria José Menezes Brito (Rev Rene)
Objective: to understand the development of moral sensitivity in the practice of Family Health Strategy professionals. Methods: a unique case study, of qualitative approach, conducted with thirty-five professionals from the family health teams. Data collection occurred through interviews guided by semi-structured script and observation. The data was analyzed through Thematic Content Analysis. Results: the analysis revealed that factors related to work organization, interpersonal relationships and personal values influence the development of the moral sensitivity of professionals in family health teams. Conclusion: the development of the moral sensitivity of Family Health Strategy professionals is influenced by enabling and hindering factors that present themselves in daily work.